Detection of Aruco Markers Using the Quadrilateral Sum Conjuncture - Ferrão, José (2018)
Fiducial Markers are heavily used for pose estimation in many applications from robotics to augmented reality. In this paper we present an algorithm for the detection of aruco marker at larger distance. The algorithm uses the quadrilateral sum conjecture and analyzes the sum of the cosine of the internal angles to detect squares at larger distances. Experiments conducted showed that the developed solution was able to improve the detection distance when compared to other methods that use similar marker while keeping similar pose estimation precision.